PISICHIK DEVELOPMENT OF BEHAVIOR IN PRESCHOOL CHILDREN - Madgafurova Dilfuzakhan Okhunovna (American Journals Publishing, 2023)
Preschool years are a very important period for the development of behavior in children. During this period, children begin to establish the world around them, form relationships, learn social norms, develop emotional and self-regulatory skills. In this article, we will study various aspects of the development of behavior in preschool children.
Keywords: school, behavior, preschool education, complex, emotional development.